Characterization of didactic and pedagogical training in Brazilian stricto sensu Postgraduate Programs in Nursing - Katheri Maris Zamprogna; Vânia Marli Schubert Backes; Jouhanna do Carmo Menegaz; Bruna de Souza Francisco
ABSTRACT Objective: To characterize the didactic and pedagogical training offered in Brazilian stricto sensu Postgraduate Programs in Nursing. Method: Descriptive, documentary research, based on data from 30 postgraduate programs that offer an academic master's degree and a PhD degree. We collected the course projects and teaching plans of the disciplines related to didactic and pedagogical training, accessed through the Sucupira Platform or the institutional website. The variables were analyzed by descriptive statistics, through calculations of relative and absolute frequency. Results: Regarding the lines of research of the programs, it was evidenced that 17.4% (n=20) were related to didactic and pedagogical training, 9.4% (n=3) followed this approach and, regarding compulsory didactic and pedagogical disciplines, it was observed that they were expressed differently in the curricula of masters and PhD courses, since part of the masters courses (56.6%, n=17) and of the PhD courses (76.6%, n=23) did not have this requirement. Conclusion: There should be a Brazilian guideline to promote the didactic and pedagogical training of university professors.